The time-crunched cyclist : race-winning fitness in 6 hours a week - Carmichael, Chris, ....-; Rutberg, Jim, ....- (Boulder : VeloPress, 2017)
The Time-Crunched Cyclist reveals the fastest way to get fit for road racing, century rides, gravel grinders, cyclocross, Gran Fondos, and mountain bike events. With elite cycling coach Chris Carmichaels innovative, time-saving approach, busy cyclists will develop fitness, speed, and power in just 6 hours a week. Now powered by Strava, this updated third edition of The Time-Crunched Cyclist training program taps into the most popular cycling social network to help cyclists get fired up to crush their workouts, one segment at a time. Through his popular endurance coaching service, Carmichael noticed that many busy cyclists are unable to make performance gains using conventional training methods; they simply dont have enough time to train. So CTS developed a new approachthe Time-Crunched Training Programto help cyclists achieve competitive fitness and power without the impossible time demands of traditional training methods. The Time-Crunched Cyclist shows cyclists how to build fitness on a realistic schedule by tapping the power of high-intensity interval training (HIIT) workouts. Cyclists learn the science behind this alternative approach to training before performing the CTS field tests to get a baseline reading of their fitness. Nine comprehensive training plans include effective time-crunched workouts, nutrition guidelines, and strength training to develop the speed and endurance for a wide variety of cycling races and events.
Keywords: Wielrennen